Bagaimana Kondisi Internal dan Eksternal Memengaruhi Mahasiswa Akuntansi menjadi Wirausahawan - Ardiansyah, Muhammad Rifki; Suryantara, Adhitya Bayu (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to determine the influence of internal and external factors on the entrepreneurial interest of accounting students. This research method uses a quantitative method with a sample of accounting students as many as 150 respondents with a sampling technique using purposive sampling. Data collection is through questionnaires or questionnaires, and data is measured using a Likert scale. The data analysis technique uses SmartPLS 4 with the Structural Rural Equation Modeling (SEM) method. The results of the study showed that the variables of employment conditions, e-commerce and capital availability had a positive and significant influence on students' entrepreneurial interests, while the variables of mental accounting and family environment did not have a significant effect on students' entrepreneurial interests.